The role of drop shape in impact and splash - Qingzhe Liu (Nature Portfolio, 2021)
The dynamics of droplet impact and splash is important in many applications, yet its analysis involves difficult intertwined aspects. Here Liu et al. make shape parametrically accessible to experiment, with ferrofluidic drops passing a magnetic field in a defined way.